What went wrong with sports diplomacy? - CANTU REYNA URQUIDI, Tabatha Melissa (KDI School, 2021)
Sports diplomacy enhances a nation's positive image through soft power. However, this research suggests an alternative outcome for sports diplomacy in which a country's international sports relations leave a non-favourable impression. This research analyses Mexico's international sports governance and its effects on sports diplomacy, intending to identify the factors that end with a negative national brand image. To do so, it reconstructs the central components of sports diplomacy, highlights the role of athletes as actors and the impact of social media platforms for national promotion, and analyzes multiple studies-cases about Mexican international sports governance occurring over 2019-2020. Based on those studies-cases, a panel of experts through a SWOT matrix analyzes Mexico's national projection through sports. Then, opportunities and threats found are reviewed through the PESTEL analysis tool. By doing so, this research contributes to the sports diplomacy field and serves sports and nation-branding practitioners.
Thesis(Master) -- KDI School: Master of Public Policy, 2021
Keywords: Diplomacy--Social aspects